Evaluating the toxicity properties of Sesbania grandiflora ethanolic extract on zebrafish embryo - Ismail, Elysha Nur; Sarchio, Seri Narti Edayu (2024)
Sesbania grandiflora (SG), also known as the vegetable hummingbird, is widely used in traditional medicine due to its rich phytochemical profile. This profile has shown promise in treating a variety of ailments, including antibacterial, anthelmintic, and antineoplastic effects. This study represents the first investigation into the toxicity effects of S. grandiflora ethanolic extract (SGE) during embryonic development. Zebrafish (Danio rerio) embryos serve as ideal subjects for toxicity testing due to their rapid development, transparency, and approximately 70% genetic similarity to humans. While there have been publications emphasizing SG toxicity, research on toxicity properties during embryonic developmental stages remains limited.